FACTORS INFLUENCING THE ADOPTION OF CLIMATE SMART AGRICULTURAL PRACTICES AMONG IRISH POTATO FARMERS IN PLATEAU STATE, NIGERIA - Goni, I. C.; Garba, M.; Bose A. A.; Abdullahi, S. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
The study examined the factors influencing the adoption of climate smart (CSA) agriculture among Irish potato farmers in Plateau State, Nigeria. A multi-stage sampling technique was used in selecting 390 respondents. Data were collected using structured questionnaire and analysed using descriptive and inferential statistics. The results revealed that more than half (51.5%) of the respondents were male with a mean age of 40.36 years. Majority (66.3%) of the respondents were married, and 52.8% had tertiary education. The mean household size, farm size and farm experience of the respondents were 6 persons, 1.4ha and 15 years respectively. Perception of respondents on climate change was the poor yield of potato (4.58). The result further revealed that farm size (P<0.01), age (P<0.05), and income (P<0.1) were the major factors that significantly influenced the adoption of climate smart agricultural practices. The major constraints to adoption of CSA were inadequate information from meteorologists (86.5%), inadequate information from research centers (79.8%), and inadequate capital (76.5%), which were ranked 1st, 2nd, and 3rd, respectively. The study concluded that adoption of CSA was influenced by factors such as age, farm size, income and yield. The study recommended that policy makers are to note farmers concerns on climate variability, small scale irrigation as CSA practices be given emphasis, private sectors should establish extension services, meteorological centers and farmers advised to form cooperatives to help them acquire low interest loans in acquiring farm inputs.